Nutritional Status Assessment Of Elderly People In A Rural Area Of West Bengal, India - Sunanda Biswas, Souti Biswas (International Journal of Advanced Science and Technology, 2020)
Background & Goals:In India The Demographic Of The Elderly Is Growing Slowly And Nutrition Is An EssentialElemental Factor For Their Wellbeing. While Malnutrition Among Elderly Patients Is AssociatedWith Several Health Effects, This Study Was Designed To Evaluate The Nutritional Status Of TheElderly Population In A Rural Area Of West Bengal, India.Materials And Methods:A Cross-Sectional Community-Based Study Was Done In Two Villages In The District Of North 24Parganas, West Bengal, It Included People Aged Up To 60 Years. Data Were Obtained Using AQuestionnaire And Anthropometric Assessments From Mini Nutritional Assessment (Mna).Results24 Percent Of The 168 Respondents Were Deficiency, 36 Percent Were At Risk Of Overweight, And40 Percent Were In Good Nutritional Health. The Median Age Of The Elderly Was 69.79± 8.69,Mean Bmi 23.75± 5.25. Females Had Been More Undernourished Than Males. Bmi And Total MnaScore Were Found To Have A Significant Relationship.Conclusion: The Present Experiment Concluded That Elderly People's Nutritional Status Was VeryLow, And There Is An Increased Need To Pay Attention And Take More Strategic Action ToStrengthen Elderly People's Nutritional Status In Rural Locations.